Analisis Publicness Theory dalam Revolusi Pelayanan Publik di Surabaya melalui Surabaya Single Window (SSW) Alfa - Arsanti Putri, Nadia; Christian, Miracle; Zahrah Supriyadi, Fajrina Nuri (Jurnal Administrasi Publik dan Bisnis, 2025)
The era of globalization encourages the government to utilize the use of internet-based information technology to provide excellent public services. The government is required to create services that are easily accessible, effective, efficient, and centralized. This research article aims to analyze the use of the Surabaya Single Window (SSW) Alfa launched by the Surabaya City Government by reviewing it through publicness theory. The research method used is a literature study as a secondary data source regarding public theory and SSW Alfa. The results of the study indicate that the SSW Alfa application can be said to be a real manifestation of digital reform in the implementation of public services at the city level. This finding indicates that this application can improve relations between the community and the government through a more modern public service network.